Peningkatan Hasil Belajar Pendidikan Agama Islam dengan Model Jigsaw Kelas VII SMP Negeri 1 Simpang Alahan Mati - Dinanda Tj Menanti; Norawati Norawati (Kampus Akademik Publiser, 2024)
Islamic Religious Education has tended to use monotonous methods and approaches, making the learning process less engaging and less active. The results of this study address various issues regarding teacher and student activities in the Islamic Religious Education learning process through the application of jigsaw in grade VII, as well as improving student learning outcomes. This research is in the form of Classroom Action Research (CAR). The research was conducted in two cycles and four stages of implementation: planning, action, observation, and reflection. Data collection was carried out through observation, testing, and documentation. The results of the study indicate that the jigsaw method of learning Islamic Religious Education on the material of the Universe as a Sign of the Power of Allah SWT. improves the learning outcomes of grade VII students in the even semester of the 2024/2025 academic year. The success of the jigsaw method implementation is known from the increase in student learning outcomes in the first cycle. Teacher activity received an average score of 2.50, categorized as quite good, student activity received an average score of 3.00, categorized as good, and student learning outcomes obtained a completeness score of 75% with a score of incomplete 25%. In the second cycle, teacher activity received an average score of 3.00, categorized as good, student activity received an average score of 3.60, categorized as very good, and student learning outcomes obtained a completeness score of 90% with a score of incomplete 10%. Students were more active and skilled in the learning process. Teachers were more skilled, varied in teaching activities, and the use of methods. In conclusion, the jigsaw model can improve student learning outcomes in Islamic Religious Education subjects, the material of the Universe as a Sign of the Power of Allah SWT.